Creating an SDG-Oriented Youth Engagement Plan: An Action Research - Bastida, Ernesto L. (Animo Repository, 2024)
Youth empowerment is one of the strong indicators of inclusive governance. The collective actions and commitment of youth toward continuous improvement are also fundamental drivers of resilient, sustainable, and progressive communities. Their consistent engagement in policymaking and sustainability planning provides a concrete potential to foster inclusive growth and to promote collaborative mechanisms useful for achieving the short-term and long-term goals of the local government. In this regard, the active participation of youth in development planning is projected to significantly contribute to the knowledge economy and the attainment of global goals. Hence, the present study aimed to create a sustainable development or SDG-oriented youth empowerment engagement plan that will be used to accelerate youth organizations’ roles in the decision-making processes and community participation. The study was conducted among selected youth organizations of different barangays in the City of Dasmariñas Cavite, Philippines. To achieve the study objective, the researchers made use of community-based participatory research in planning. This collaboration-driven research design was done in cooperation with youth organization members, policy and academic experts, local government officials, and the researchers as participants. A series of planning workshops were conducted to capacitate the youth organizations to create SDG-oriented plans. Results revealed that most of the created plans during the workshops prioritized goals such as clean and sanitation, quality education, gender equality, good health and well-being, peace and sanitation, and strong institutions. On the other hand, the least prioritized goals in their crafted plans include climate action, decent work, economic growth, and partnership for the goals. Moreover, the created youth empowerment accelerator framework emphasizes its four pillars, namely, development-oriented, participatory-focused, equity-centered, and rights-based, which are relevant to actualizing the crafted SGD-oriented youth engagement plan.